Leadership as meaning-making : the hero's journey to transformation - Varney, John, 1934- (New York : Productivity Press, 2020)
Based on the author's 30 years experience of management development and a background in design and psychology, this book takes a fresh look at leadership as a systemic shared phenomenon. It is one aspect of the evolutionary principle of bringing people to maturity as human beings - transforming the immature through purposeful adventure. This is not a how-to book of tools and techniques but is a guide to personal development. It plots the territory of the hero's journey (after Joseph Campbell) through unknown worlds. It explains the metaphorical relationship to personal and collective transformation by means of the cyclic pattern of the hero's journey, overlaid with the enneagram framework. Succeeding chapters spell out practical details for making the journey towards maturity, which alone makes leadership a viable possibility. Only such purposeful leadership will enable others to make their own equivalent journeys. If such people are engaged in work, then they will be more conscious and more effective. Essentially, the book is intentionally quickly communicates a broad sweep of related ideas that form a philosophy for the development of the inner qualities of effective leadership, applicable in all walks of life. The story of the archetypical hero's journey is suggested as applying to every individual. The hero's journey is an allegory for a quest for inner growth. It can rub off onto others through what we call leadership. Such leadership is what brings meaning to people's lives. Thus this book is a counter to the empty manipulative techniques propagated by much of the popular writing on leadership, which pays little attention to transformative interaction. There are exercises at the end of each chapter and additional material is available to readers via the internet.
Preface About the Author Foreword Introduction 1. Worlds of Perception: An Adventure in Wholeness 2. The Creative Cycle: And the Enneagram Framework 3. Being and Becoming: The Triad of Inner 4. Triad of Action: How We Show Up in the World 5. Pattern Thinking: Making Sense and Making 6. Self-Organisation: Leadership and Teamwork 7. Clarity of Vision: Strategies for Success 8. A Sense of Purpose: Making a Meaning-Field 9. Commitment: Embark on Your Hero's Journey 10. The Author's Own Journey Epilogue Bibliography Index
OCLC-licensed vendor bibliographic record.
Keywords: Leadership -- Psychological aspects; Maturation (Psychology); Success; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Skills; BUSINESS & ECONOMICS / Workplace Culture